Analyzing Energy Transition Patterns in Asia: Evidence From Countries With Different Income Levels - Farhad Taghizadeh-Hesary; Ehsan Rasoulinezhad (Frontiers in Energy Research, 2020)
Energy transition as the issue of striving to use more environmentally friendly energy sources instead of fossil fuels is a crucial debate for scholars. A key point is how macroeconomic variables can accelerate the energy transition movement in different regions, which may lead to similarities in energy transition patterns among various regions. The main purpose of this study is to determine how energy transition patterns depend on economic variables in Asian economies, classifying based on their income level. To this end, we collected the related variables for 45 economies in Asia over the period 1993–2018 and conducted estimation using the generalized method of moments (GMM) approach. The major results revealed that economic growth has a positive relationship with the energy transition, while CO2 emissions negatively influence energy transition. Furthermore, in both sub-sample groups (i.e., high and upper-middle-income and low and lower-middle-income groups) an increase in population lows the energy transition process. As an important recommendation, Asian economies with different income levels need different policies to improve and accelerate the energy transition movements. Especially in the developing and emerging economies that have higher economic growth rate and more energy demand, the governments need to implement various supportive policies for easing the access to electricity from green resources in line with the sustainable development goals (SDGs). This is more essential in the current low oil price era.